Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Fikih Kelas Ix Mts Al-Wasliyah Pangkalan Brandan - Rida Anisa; Syahrul Affan; Ahmad Fuadi (Jurnal Berbasis Sosial, 2022)
This study aims to improve students' understanding with a problem-based learning model at MTs Al Washliyah Pangkalan Brandan. The type of this research is Classroom Action Research (CAR). The object of this research is class IX students of MTs Al Washliyah Pangkalan Brandan. The object of this research is the 28 students of class IX-2. Before taking action, the researcher made observations first by interviewing the field teacher and homeroom teacher. The instruments that the researcher uses are Observation, Interview, Test and Documentation. This research was carried out in two cycles, each cycle was carried out in two meetings. In Cycle I the percentage level of students was 78.57% With 22 students who completed and 6 students did not complete. In the second cycle there was an increase in students' understanding with a percentage rate of 89.28% with 25 students completing and 3 students not completing. There was an increase of 10.07%. This shows that the implementation of the problem-based learning model is running smoothly and is considered well applied at MTs Al Washliyah Pangkalan Brandan.